1992
DOI: 10.1103/physreva.46.5706
|View full text |Cite
|
Sign up to set email alerts
|

Reexamination of theLi+-He interaction potential

Abstract: Using various recently proposed interaction potentials for the Li+-He system, elaborate calculations of the mobility, longitudinal, and transverse diffusion coefficients of Li+ swarms in helium have been made by high-speed Monte Carlo simulations (MCS s). In addition, the transverse diffusion coefficients for this ionneutral-atom pair have been experimentally measured with total errors of +3/o. The close agreement of the present experimental results with those of Skullerud, Eide, and Stefansson [J. Phys. D 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[18][19][20] The dispersion interaction can also play an important part of binding between metal ions and the rare gases. [25][26][27][28][29][30][31][32][33] The data for most transport experiments are obtained at room temperatures where the small size of Li + -RG dispersion interaction will not have much influence. [22][23][24] Experimental investigations of the transport of the Li + ion in the rare gases have prompted investigations of the interaction potentials between Li + and the rare gases.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] The dispersion interaction can also play an important part of binding between metal ions and the rare gases. [25][26][27][28][29][30][31][32][33] The data for most transport experiments are obtained at room temperatures where the small size of Li + -RG dispersion interaction will not have much influence. [22][23][24] Experimental investigations of the transport of the Li + ion in the rare gases have prompted investigations of the interaction potentials between Li + and the rare gases.…”
Section: Introductionmentioning
confidence: 99%
“…The accurate determination of the transport coefficients of gaseous ions in a neutral gas with an electric field is of fundamental importance [1,2]. In this paper, we continue the experimental measurements of the transverse diffusion coefficient-to-mobility ratio, D T /K, of alkali ion-rare gas pairs [3,5] by reporting the results for a dilute swarm of Cs + ions drifting in Ne and Ar gases at values of electric field-to-neutral gas number density ratio E/N in the range 5-600 Td and at temperature 303 ± 1 K. Monte Carlo simulation (MCS) calculations [4] are reported for mobility (K) and for longitudinal and transverse diffusion coefficient-to-mobility (D L /K and D T /K) ratios to adjudicate between the accuracies of the two available interaction potentials for these ion-neutral species pairs, namely those due to Koutselos, Mason and Viehland (KMV) [6] and the modified Tang-Toennies (MTT) [7] calculations, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, there is a dearth of experimental data for D T or D T /K of sufficient accuracy. [3][4][5][6][7][8][9][10][11][12][13][14][15] The only experimental data reported for both Rb ϩ -Kr and Rb ϩ -Xe systems are values of the reduced mobility ͑K 0 ͒, 16 and the product of the neutral gas number density and longitudinal diffusion coefficient ͑ND L ͒. 17 These data were compiled in numerical form by Ellis et al 18 To our knowledge, no transverse diffusion data has yet been reported for Rb ϩ ions drifting in Kr and Xe gases.…”
Section: Introductionmentioning
confidence: 99%